2017
DOI: 10.1155/2017/8302636
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory and Neuroprotective Role of Natural Product Securinine in Activated Glial Cells: Implications for Parkinson’s Disease

Abstract: Glial activation and subsequent release of neurotoxic proinflammatory factors are believed to play an important role in the pathogenesis of several neurological disorders including Parkinson's disease (PD). Inhibition of glial activation and inflammatory processes may represent a therapeutic target to alleviate neurodegeneration. Securinine, a major natural alkaloid product from the root of the plant Securinega suffruticosa, has been reported to have potent biological activity and is used in the treatment of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 35 publications
(37 reference statements)
1
37
0
Order By: Relevance
“…The increase in enzymes activity may be due to an indicator of liver injury or dysfunction [31]. Aluminum exposure can result in its accumulation in the liver and leads to liver damage because of increased enzymes levels in the serum [32]. The present data showed that serum creatinine and uric acid levels increased in Aluminium exposure group, which is accurately linked with the renal function dysfunction.…”
Section: C1 Reg Controlsupporting
confidence: 49%
“…The increase in enzymes activity may be due to an indicator of liver injury or dysfunction [31]. Aluminum exposure can result in its accumulation in the liver and leads to liver damage because of increased enzymes levels in the serum [32]. The present data showed that serum creatinine and uric acid levels increased in Aluminium exposure group, which is accurately linked with the renal function dysfunction.…”
Section: C1 Reg Controlsupporting
confidence: 49%
“…Pharmacological studies have shown that S. suffruticosa can promote blood circulation, relax the muscles and tendons, invigorate the spleen and kidney, and relieve rheumatic pains. Moreover, this shrub is effective for the treatment of neurasthenia, facial nerve paralysis, post-polio syndrome, dizziness, deafness, narcolepsy, impotence, and acute liver injury, and other diseases [7][8][9][10]. It possesses an extremely high application value [4].…”
Section: Introductionmentioning
confidence: 99%
“…Securinine (Sec) was first extracted, purified, and structurally characterized from the roots of Securinega suffruticosa in 1963 and has been traditionally used in oriental medicine. Sec has been reported to inhibit inflammation and neuronal damage in activated neuroglial cells (Leonoudakis et al, 2017). Sec has been developed as a drug to treat neurological conditions such as ALS, polio, and multiple sclerosis (Buravtseva, 1958).…”
Section: Introductionmentioning
confidence: 99%